The Reality of Healthcare Services in the Algerian Health Sector Amid Digital Transformation :A Case Study of Mohammed Boudiaf -Ouargla- (Journal of Economic Additions, 2025)
This study examines the state of healthcare services in Algeria amid increasing adoption of digital technologies. It aims to evaluate the extent of digitalization and its impact on service quality in healthcare institutions.Using a descriptive-analytical approach supported by field data, the study reveals no disparities in implementation levels and highlights challenges such as weak infrastructure and limited staff training.Findings suggest that while digitalization offers clear benefits, its full potential is hindered by technical and organizational barriers. The study provides recommendations to better align national digital strategies with actual practices in Algerian healthcare settings. Jel Classification Codes : J24, I18.
Keywords: Keywords: Digitalization; Healthcare services; Healthcare service quality.